Evaluation of the strain energy density control volume for a nanoscale singular stress field. Issue 12 (21st April 2016) - Gallo, P; Sumigawa, T; Kitamura, T; Berto, F
Abstract: Fracture mechanics at micro‐ and nano‐scale has become a very attractive topic in the last years. However, the results are still few, mostly because of the lack of effective analytical tools and of the difficult to conduct experimental tests at those scales. In this study, the authors report preliminary analysis on the application of the Strain Energy Density (SED) method at nano‐scale. In detail, starting from mechanical properties experimentally evaluated on small single crystal silicon cracked specimens, a first evaluation of the control volume due to a nano‐size singular stress field is carried out. If the extension of the SED approach at micro‐ nano‐scale is given in near future, an easy and fast tool to design against fatigue will be provided for micro‐ nano‐devices such as MEMS and NEMS, resulting in a significant technological impact and providing an easy and fast tool to conduct static and fatigue assessment at micro‐ and nano‐scale.